Design of a static output feedback H-infinity controller for linear time-invariant systems: An LMI approach - Parlakci, M.N.A. (Institute of Electrical and Electronics Engineers Inc., 2018)
This note is concerned with the static output feedback (SOF) H-infinity controller design for linear timeinvariant systems. A sufficient bilinear matrix inequality (BMI) condition is developed for finding a stabilizing static output feedback H-infinity controller. For the first time, a novel cone complementary linearization approach within the context of linear matrix inequalities (LMI) is proposed to investigate the feasibility of the stabilizing controller synthesis along with a minimized H-infinity attenuation rate. The proposed method requires neither any apriori assumption generally made on the input/output matrices nor any application of a coordinate transformation. An example is presented for the application of the proposed scheme. © 2018 IEEE.
ASTI Automation SRL;Continental Automotive Romania SRL;Electro-Total SRL
22nd International Conference on System Theory, Control and Computing, ICSTCC 2018 -- 10 October 2018 through 12 October 2018 -- -- 142926
Keywords: Cone Complementary; Linear Matrix İnequalities; Static Output Feedback; Computation Theory; Controllers; Feedback Control; Invariance; Linear Control Systems; Linear Systems; Linear Transformations; System Theory; Time Varying Control Systems; Attenuation Rate; Bilinear Matrix Inequality(Bmı); Co-Ordinate Transformation; Cone Complementary Linearization; H-İnfinity Controller; Linear Time İnvariant Systems; Stabilizing Controllers; Static Output Feedback; Linear Matrix İnequalities